MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM MELALUI MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Muslimah, Yuliatun (Vidya Karya Jurnal Kependidikan, 2012)
This research relates to the implimentation of STAD model in State Senior High School 2 (SMAN 2) Tanjung. The research objective is to increase the studentsâ learning activity and teacherâ activity quality as well as to increase the studentsâ achievment on hydrolysis salt material. The research is based on the classroom action research (CAR) through 2 cycles. The research subject is 33 students of second class majoring on natural science in SMAN 2 Tanjung. The data collection used studentsâ and the teacherâs activity obeservation sheets as well as achievment result. The data were qualitatively analyzed with percentage technique. The result of research stated that (1) studentsâ activity underwent progress in the first cycle and that described 10 activities that achieve the activeness percentage, namely more than 85%, whereas in the second cycle studentsâ activity turned into 14 activities; (2) the quality of teacherâs activity was higher or 80,7% in the second cycle than in the first cyle, namely 79,5%; and (3) the completeness of studentsâ learning increased from 73% into 91%. The groupâs score increased in the first cycle; there were not groups that had super quality, but there was 1 group that had great quality in the second cycle.